Decline and Fall - Waugh E. Evelyn (The millennium library)
Sent down from Oxford in outrageous circumstances, Paul Pennyfeather is oddly surprised to find himself qualifying for the position of schoolmaster at Llanabba Castle. His colleagues are an assortment of misfits, rascals and fools, including Prendy (plagued by doubts) and Captain Grimes, who is always in the soup (or just plain drunk). Then Sports Day arrives, and with it the delectable Margot Beste-Chetwynde, floating on a scented breeze. As the farce unfolds and the young run riot, no one is safe, least of all Paul.